Usage attitude among food and beverages small medium enterprises towards halal mobile application in Sabah, Malaysia - Haslinda Hasan (2023)
The general function of the Halal Mobile Application (HMA) is to verify the Halal status of a product. However, the overarching idea is to provide access to a larger market and more transparency for those who conduct Halal business. This study was designed to examine the usage attitude among food and beverage Small and Medium Enterprises (SMEs) towards Halal mobile application in Sabah. Previous studies on Halal and mobile applications mainly addressed the Halal issue from the consumer's perspective, whereas this study addresses the HMA issue from the industry players' perspective (SMEs). The evolution of the Halal approach and the response of SMEs in Sabah to HMA as a tool to improve their Halal development programme were also discussed. The four objectives of the study are: (i) To examine the relationship between value images (Halal and social responsibility) and trajectory images (perceived consumer effectiveness and goals) towards usage attitudes of Halal mobile applications; (ii) To investigate the relationship between trajectory images (perceived consumer effectiveness and goal), and strategic images (relative advantage, perceived usefulness and perceived ease of use); (iii) To analyze the usage attitude of Small and Medium Enterprises of food and beverage with regard to mobile Halal applications based on Image theory; and (iv)To investigate perceptions of Halal among Small and Medium Enterprises in the food and beverage industry and attitudes towards the use of Halal mobile applications in Sabah. The research model was developed based on image theory and the adoption process. This study also bridges the interdisciplinary gap between Image theory for human decision making and the diffusion of innovation. Questionnaires were distributed to 200 SMEs in Sabah using the convenience sampling method. Of the questionnaires, a total of 186 were returned completed, representing a response rate of 93%. The research model was analysed using SPSS v27 and PLS-SEM. The results show that the relationship between social responsibility and goal is the strongest (0.516) and that perceived usefulness and acceptance of HMA is the weakest (-0.051). All errors of the PLS model were lower than those of the LM model. Therefore, we can conclude that the model has strong predictive power. Findings and discussion of this research will help SMEs, policy makers and researchers to find solutions, make suggestions and formulate the appropriate plans or decisions for SMEs related to HMA. This study is one of the first to address the issue of SMEs and HMA in Sabah. Moreover, this study assumes that the Halal concept is not only for marketing purposes but also as Fardhu Kifayah for Muslim food producers. Overall, this empirical study provides a valuable basis for further studies on the Internet of Things and SMEs in Sabah in particular and Malaysia in general. The study indicated that SMEs in Sabah have a positive attitude towards the use of HMA. The majority of SMEs surveyed in this study indicated that they are willing to use HMA to promote their business, improve productivity and manage their businesses. However, the use of HMA by SMEs in Sabah remains low due to a lack of awareness and a suitable business model. To increase the use of HMA among SMEs in Sabah, the study recommends that government agencies and industry players take proactive steps to educate and promote the use of these apps. In addition, better business models and incentives need to be put in place to encourage SMEs to use HMA.